XINJIANG HUMAN RIGHT VIOLATION AND RADICALISM ISSUES : A DEVELOPMENT INEQUALITY FRAMING - Ahmad Amiruddin Tennang, Andi Ismira (Jurnal Mandala, 2019)
This Article aiming to discuss about recent Human Right Situation of Uyghur People in Xinjiang Province and the logic of powerful and structural effort by Beijing’s Authority to push “De-Extrimification” through “Strike Hard” program. A situation where, non-Chinese societies being forced to conform to Chinese culture, particularly that of the ethnic Han majority. The policies, politically seems like a will to annihilate identity of a society to determine their destiny, and to re-establish themselves in future generations. This writing also eager to examine, what was the driving factor the radicalism acts which has been occur in Xinjiang since over centuries, that this Radicalis has dragging the Chinese government to put the Policies on stage and seems not going to be downwarded. Using, Descriptive Analityc methods, this article analize the Uyghur and Xinjiang situation with geo-politic, development inequality and human security concepts.